Relação entre trabalho e necessidades de saúde de moradores adscritos a uma unidade de saúde da família do município da Serra-ES - Poldi, Roberta Melo Vello (2008)
The study aimed at identifying and analyzing the health needs in the point of view of the ones living in Serra/ES district, with different occupational insertions and added in writing in a health family unit of the same district. The research was exploratory, with a qualitative approach, based on focal groups, composed by civil construction workers and maids. It uses the thematic analysis, having as theoretical-conceptual referential the Matsumoto’s (1999) Taxonomy of Health Needs (1999) and the identification of two themes: the relation between work and health-disease process and the relation between health needs and the use of health services. Data show that the work is, above all, a necessity to survive, interfering directly in the study time and pleasure, impacting directly on the health-disease process. It presents a pluralist and holistic vision of this process, articulated with the material conditions of existence, highlighting that health is the same of having good conditions of life and the tranquility that comes with it. About the use of the services given by the district health family unit, it points problems such as: the delay and the difficulty in getting an appointment; the lack of professionals and of necessary equipment; the number of vacancies offered lower than the demand; the unit working schedule that coincides with the worker’s labor hours; the lack of the services integration of reference and against-reference. It stands out the necessity to guarantee the access to all available technologies. The people living in the district demonstrate the autonomy in the way they live life, when they use, besides the services considered as belonged to the official Medicine, popular measures, like homemade Medicine, the medical-religious practices, the auto medication and the pharmacist assistance. Despite noticing little preoccupation and responsibility of the unit professionals considering their health, they value the relational dimension of care, emphasizing the listening capacity, showing the necessity of being linked to a professional or to the health team. Despite the health conscience as a right and the necessity to participate in the community fight for such right accomplishment, the public service of health does not give space and time conditions so that, in the participative instance ambit, can emerge the characteristics of social tessitura in which are inserted, having the work as center. The research raises questions that contribute for the inclusion of health ocupational actions in primary health care, more specifically in ESF. Directing these services in the satisfaction logic of health, in their users’ optic, presents a potential of giving visibility to work as one of the determining factors of the health-disease process, not reducing the health actions of the worker to the assistance dimension, rescuing the protagonism of the worker in the construction of integrality of health assistance.